Implementation of Learning Models Project Citizen by Utilizing Wakelet Media Can Enhancing Student Collaboration and Responsibility Public High School 2 Sidoarjo - Ristiarni, Rima; Jatiningsih, Oksiana (International Journal of Emerging Research and Review, 2026)
Objective: This study was conducted to analyze the effectiveness of the Wakelet media-assisted citizen project learning model in improving student collaboration and responsibility in class XII of Public High School 2 Sidoarjo and to identify student responses. towards the citizen project model learning assisted by Wakelet media. Method: The research method used is a quasi-experimental with a non-equivalent control group design. Involving one experimental class that received project learning and one control class with conventional learning. Data collection was conducted at Public High School Negeri 2 Sidoarjo East Java. Data collection techniques included pretests and posttests (to measure students' collaboration and responsibility abilities), student questionnaires (to measure students' responses to Wakelet-assisted citizen project learning), and observations to record collaboration and responsibility behaviours during the learning process. Results: shows a significant increase in the experimental class, as shown by the average pre-test value of 75.95 increasing to 85.95 in the post-test. Student responses to the learning were in the very positive category, especially in the aspects of collaboration, visual appeal, and ease of publishing digital projects through Wakelet. Novelty: This research lies in the systematic integration of the Wakelet digital platform in Project Citizen documentation to increase collaboration and responsibility of high school students.” This study uses Wakelet as a medium for presenting project-based citizen and responsibility- based materials , as well as a collaboration facilitator. Furthermore, this study introduces a learning design that has not been widely explored in the context of immersive learning in secondary schools.